Perineural invasion, Gleason score and prostate specific antigen; is there any association? - Mohammad Yazdani; Ali Karami; Emadeddin Yazdani-Kachouei; Farhad Tadayon (Journal of Nephropathology, 2019)
Introduction: Prostatic cancer is one of the most common malignancies among males. Perineural invasion (PNI) is a common finding of prostate cancer associated with more aggressive malignancies. Objectives: The current study was conducted to assess the association of PNI with serum prostate specific antigen (PSA) and Gleason score. Patients and Methods: This analytical cross-sectional study conducted on 354 known cases of prostatic cancer (2015 until 2017). Patients’ last PSA and Gleason score wit h presence/lack of PNI in their prostate biopsies were recorded. The association of PNI with PSA and Gleason score was assessed. Results: Serum level of PSA and Gleason core were significantly higher in patients with PNI (P< 0.001 for both). Gleason score was independently a predictor of PNI (odds ratio [OR]: 3.05, 95% CI:2.32- 4.001; P=0.001). Serum PSA level of 17 ng/mL had specificity of 90.3% and sensitivity of 42.7% for prediction of PNI. Conclusion: In this study we found, Gleason score is independently a prognostic factor of PNI among cases undergone prostate biopsy. In addition, serum PSA level of 17 ng/mL was 90.3% specific and 42.7% sensitive for PNI occurrence. However, our findings require further evaluations by larger studies.